The Emerging Role of Natural Killer Cells in Innate and Adaptive Immunity - Kim, Eun-Mi; Ko, Chang-Bo; Myung, Pyung-Keun; Cho, Daeho; Choi, Inpyo; Kang, Hyung-Sik (Immune network, 2004)
In the early host defense system, effector function of natural killer (NK) cells results in natural killing against target cells such as microbe-infected, malignant, and certain allogenic cells without prior stimulation. NK cell cytotoxicity is selectively regulated by homeostatic prevalence between a repertoire of both activating and inhibitory receptors, and the discrimination of untransformed cells is achieved by recognition of major histocompatibility complex (MHC) class I alleles through inhibitory signals. Although it is well known that the bipotential T/NK progenitors are derived from the common precusor, functional mechanisms in terms of the development of NK cells remain to be further investigated. NK cells are mainly involved in innate immunity, but recent studies have been reported that they also play a critical role in adaptive immune responses through interaction with dendritic cells (DC). This interaction will provide effector functions and development of NK cells, and elucidation of its precise mechanism may lead to therapeutic strategies for effective treatment of several immune diseases.